2017
DOI: 10.1200/jco.2017.35.15_suppl.2561
|View full text |Cite
|
Sign up to set email alerts
|

A phase Ib/II clinical trial of a novel oxygen therapeutic in chemoradiation of glioblastoma.

Abstract: 2561 Background: Tumor hypoxia limits the response of glioblastoma multiforme (GBM) to radiotherapy (RT) and chemotherapy (temozolomide[TMZ]). Additionally, patient biomarkers are strong predictors of responsiveness to TMZ. The purpose of this study is to evaluate the use of a novel oxygen therapeutic, dodecafluoropentane emulsion (DDFPe), in chemoradiation treatment of GBM and stratify the results based on predicted TMZ response. Methods: 11 adult GBM patients have been enrolled. Patients were administered D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…NVX-108 was tested in an Australian Phase Ib/II dose finding, pharmacodynamic study of NVX-108 combined with radiation and TMZ in patients with newly-diagnosed GBM (NCT02189109). 82 All patients received standard chemoradiation consisting of 30 fractions of focal brain radiation (total 60 Gray, given as 2 Gray fractions, 5 days per week for 6 weeks) with concurrent oral TMZ at a dose of 75 mg/m 2 day, 7 days per week for 6 weeks. NVX-108 was administered by i.v.…”
Section: Nvx-108 As a Radiosensitizermentioning
confidence: 99%
See 1 more Smart Citation
“…NVX-108 was tested in an Australian Phase Ib/II dose finding, pharmacodynamic study of NVX-108 combined with radiation and TMZ in patients with newly-diagnosed GBM (NCT02189109). 82 All patients received standard chemoradiation consisting of 30 fractions of focal brain radiation (total 60 Gray, given as 2 Gray fractions, 5 days per week for 6 weeks) with concurrent oral TMZ at a dose of 75 mg/m 2 day, 7 days per week for 6 weeks. NVX-108 was administered by i.v.…”
Section: Nvx-108 As a Radiosensitizermentioning
confidence: 99%
“…TOLD MRI showed significant decrease in T1 in tumor tissue (P=0.015) with no significant change in normal brain tissue. 82 The Phase Ib/II study consisted of an initial dose exploration phase with a starting dose of 0.05 mL/kg and a dose expansion phase at the MTD of 0.1 mL/kg. An accelerated dose-escalation scheme was employed, using NVX-108 dose levels of 0.05, 0.1, 0.17, 0.25 and 0.35 mL/kg.…”
Section: Nvx-108 As a Radiosensitizermentioning
confidence: 99%
“…A variety of systemic approaches for overcoming tumor hypoxia immediately prior to therapy have been proposed including hyperbaric chambers, carbogen breathing, erythropoietin injections, and pharmacological agents such as pentoxifylline and nicotinamide to increase blood flow, but these have failed to successfully translate clinically (1216). More recent research efforts that now target more focused approaches such as pharmacologic respiratory inhibition or oxygen scavengers entrapped within the tumor to inhibit the rate of oxygen consumption (1719). Ultrasound-sensitive microbubbles containing oxygen (SE61O 2 ) for localized O 2 delivery prior to radiation therapy have been previously proposed by our group (20).…”
Section: Introductionmentioning
confidence: 99%
“…Sonus Pharmaceuticals licensed the rights for DDFPe to NuvOx Pharma (Tucson, Arizona), which repurposed its development as an oxygen therapeutic for indications such as stroke and TBI, and as a radiosensitizer to treat glioblastoma multiforme (GBM). DDFPe has been tested at doses of 0.05, 0.1, and 0.17 ml/kg (0.001, 0.002, and 0.0034 g DDFP/kg) in a Phase Ib/II clinical trial for GBM [11] and has been shown to be safe in humans at three doses of 0.17 ml/kg administered 90 min apart in a Phase Ib/II trial in acute ischemic stroke patients.…”
Section: Introductionmentioning
confidence: 99%